Nerve Block Research in Diabetic Foot Ulcers: Concerns and Suggestions [Response to Letter] - Wei Q; Dai W (Journal of Pain Research)
Qiufeng Wei, Weixin Dai Department of Anesthesiology, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Province, 530021, People’s Republic of ChinaCorrespondence: Weixin Dai, Department of Anesthesiology, The First affiliated Hospital of Guangxi Medical University, No. 6 of Shuangyong Road, Nanning, Guangxi Province, 530021, People’s Republic of China, Tel +86 13507713016, Email yfy003902@sr.gxmu.edu.cn